Kadar Proksimat dan Organoleptik Patty Ikan Barakuda (Sphyraena obtusata) dengan Penambahan Tepung Euchema cottoni - Siti Nur Aisyah Jamil; Ika Junia Ningsih; Astri Iga Siska (Samakia : Jurnal Ilmu Perikanan, 2026)
A patty is a slice of meat that serves as the filling in a burger. It is usually made from beef, but fish-based patties are rarely found. Barracuda is a type of savory fish with a low fat content, making it a potential raw material for patty production. The aim of this study was to determine the formulation of barracuda fish patties (Sphyraena obtusata) with varying proportions of Eucheuma cottonii seaweed flour based on panelists' preferences. In addition, the study aimed to examine the effect of adding E. cottonii seaweed flour on the proximate composition of barracuda fish patties (Sphyraena obtusata). The method used in this study was a quantitative experimental laboratory approach. The experimental design employed was a Completely Randomized Design (CRD) consisting of one factor with five levels of treatment, which were different ratios of barracuda fish and seaweed flour. The treatments were: P1 (100%:0%), P2 (95%:5%), P3 (90%:10%), P4 (85%:15%), and P5 (80%:20%), with each treatment replicated four times. The tested parameters included organoleptic properties color, aroma, taste, and texture as well as chemical properties such as protein, fat, moisture, ash, and carbohydrate content. The results showed that panelists preferred P1, the patty without seaweed flour addition. The addition of seaweed flour led to a decrease in protein, fat, and moisture content but increased ash and carbohydrate content in the fish patties. Therefore, from an organoleptic standpoint, panelists favored the patties without seaweed flour.